Farmers’ duties in the light of Pope’s Francis Encyclical Laudato Si’ - Kowalski, Ryszard; Grott, Edward (Studia Ecologiae et Bioethicae, 2016)
his article analyzes Pope Francis’s encyclical Laudato Si’. This analysis has been conducted with focus on how axiology and deontology of agriculture are considered in the Pope’s work. Numerous quotations from the encyclical have been included in the article to objectively present the Pope’s idea. The article primarily emphasizes these parts of the encyclical which discuss the complex genesis of the ecological crisis, having its roots in the moral downfall of men, destruction of interpersonal relationships, and breaking the bond with God. The article also shows the results of surveys carried out among farmers to demonstrate the state of ecological awareness in this professional group, as awareness plays a significant role in the implementation of Pope’s ideas on the grounds of agricultural practice. The article concludes that there still is hope and a chance are to stop the ecological crisis, but this would require a change in behavior and a limitation of technocratic thinking and consumptionism as well as replacing conformism with an active life, lived in line with the Gospel.